Study protocol of a randomized controlled trial to assess HIV/AIDS education intervention on knowledge, attitude and practices among primary school teachers - Mustapha, Abdu; Ismail, Suriani; Md Said, Salmiah; Ibrahim, Faisal; Syed Hassan, Syed Tajuddin; Yakasai, Musa Garba (Globeedu Group, 2017)
Aim: To develop, implement the HIV/AIDS educational intervention on knowledge, attitude and practices for primary school teachers in Bichi local government of Kano State, Nigeria and evaluate its effectiveness based on Information-Motivation-Behavior Skills (IMB) Model. Methods: Randomized controlled trial design will be applied in Bichi local government of Kano State, Nigeria with 600 primary school teachers randomly selected. Teachers will be randomized into either intervention group and control group. Module on HIV/AIDS education based on IMB model, will be developed and delivered to the intervention group, while talks on carrier guidance will be offered to control group. Data on HIV/AIDS knowledge, attitude and practices will be collected using validated self administered questionnaire. Data Analysis: Data will be analysed using statistical package of social sciences (SPSS version 22.0). The level of statistical significance will be set at p < 0.05 for all statistical analysis. The assessment will consist of a baseline measurement, post-intervention 1 and post-intervention 2 respectively. Descriptive characteristics of the respondents will be obtained as means, standard deviation, frequency and percentage. For analytical statistics: Pearson Chi-Square will be used for categorical data and T-test for continuous data. General Linear Model (GLM) Repeated Measure to evaluate mean differences for the intervention group and control group. Also, multivariate analysis (MANCOVA) will be used to assess statistical differences on continuous dependent variables (KAPs) by an independent grouping variables while controlling for covariates. Discussion: This theory based intervention will contribute in increasing HIV/AIDS knowledge, attitude and preventive practices among the primary school teachers in Bichi local government of Kano State, Nigeria.